Free 25-Vitamin D Is Correlated with Cardiovascular Events in Prevalent Hemodialysis Patients but Not with Markers of Renal Mineral Bone Disease - Xin Chen; Yong-Ping Lu; Ting Luo; Hong-Wei Wu; Su-Fen Cai; Mei Tian; Liang-Hong Yin; Bernhard K. Krämer; Fan-Na Liu; Berthold Hocher; Saban Elitok (Kidney & Blood Pressure Research, 2019)
Free vitamin D is the biologically active form of vitamin D. Vitamin D deficiency is associated with cardiovascular disease, the most common cause of mortality in hemodialysis patients. The goal of our current study was to investigate the relation between blood concentrations of free 25-hydroxyvitamin D with cardiovascular events in end-stage chronic kidney disease patients on hemodialysis, because this is unknown so far. We measured free vitamin D levels in 117 stable consecutive prevalent patients in September as a surrogate of vitamin D exposure during the past 6 months, and recorded the number of cardiovascular events during the previous 6 months defined as hospitalization due to heart failure, episodes of acute coronary syndrome, and stroke. Fourteen events occurred during the observation period. In patients without any cardiovascular events the free vitamin D levels were significantly higher as compared to those with cardiovascular events (patients without events: 5.68 [4.37–9.27] pg/mL; patients with events: 4.74 [3.46–5.37] pg/mL, p = 0.015). This finding remained stable after multiple regression analysis considering confounding factors such as age, time on dialysis, preexisting diabetes, hypertension, and coronary heart disease. In conclusion, our study shows that free vitamin D serum concentrations are independently associated with major cardiovascular events in chronic kidney disease patients on dialysis.